ANALISIS PROSES KOGNITIF PEMBELAJARAN TAHFIDZ AL-QUR’AN DALAM PEMBENTUKAN KARAKTER RELIGIUS SANTRI PONDOK PESANTREN AL-MIZAN - Andis Suha Fadhilah; Abdul Malik Karim Amrullah; Muh. Hambali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the cognitive process in Tahfidz Al-Quran learning and its implications for the formation of students' religious character at Pondok Pesantren Al-Mizan Muhammadiyah Lamongan. The main focus of this study lies in how time management and memorization methods are systematically managed through the perspective of cognitive learning theory. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that the implementation of tahfidz at Al-Mizan applies a "trilogy of time" (morning, afternoon, and evening) that aligns with the students' biological rhythms and mental readiness. The cognitive processes involved include the encoding phase through the chunking method, storage through intensive takrir, and retrieval through talaqqi and spatial memory reinforcement via consistent mushaf usage. The study concludes that this structured cognitive habituation effectively shapes students' religious character, such as discipline, patience, and intellectual honesty. This research contributes to the development of neuropsychology-based tahfidz learning models for character strengthening in Islamic educational institutions.